The new political economy : the public use of the private sector - Smith, Bruce L. R. (London : Macmillan, 1975)
This book, ultimately an exercise in political theory, explores the complex inter-relationships between government and other institutions participating in the policy process - universities, health care providers, corporations, voluntary societies, multinational firms and others.
"Distributed in the United States by Halsted Press, a division of John Wiley & Sons, inc., New York."
Includes bibliographical references and index.
rpm 01/11/2017
Loans
Keywords: Public interest; Public contracts; Finance, Public